A general higher-order shear deformation theory for buckling and free vibration analysis of laminated thin-walled composite I-beams. (1st September 2022) - Bui, Xuan-Bach; Nguyen, Trung-Kien; Nguyen, Ngoc-Duong; Vo, Thuc P.
Abstract: A general higher-order shear deformation theory for buckling and free vibration analysis of laminated thin-walled composite I-beams is proposed in this paper. It is based on a unified nonlinear variation of shear strains in the wall thickness and then theoretical formulation is derived in the general form which can recover the previous conventional theories such as classical and first-order thin-walled beam theory. Series-type solutions with hybrid shape functions are developed for different boundary conditions. Numerical examples are performed on laminated thin-walled composite I-beams with arbitrary lay-ups. Effects of transverse shear strains, fiber angles and slenderness ratio on the critical buckling loads and natural frequencies of the beams are reported.